Determinants of the blue economy growth in the era of sustainability: A case study of Indonesia - Taufiq Marwa; Mu'izzuddin; Abdul Bashir; Sri Andaiyani; Afriyadi Cahyadi (Economies, 2024)
The Sustainable Development Goals (SDGs) represent a fundamental global commitment to addressing a wide range of socio-economic and environmental challenges. A key component of these goals is the commitment to ocean sustainability, encapsulated in the concept of the blue economy. The blue economy, emerging in an era characterized by intricate dynamics and openness to transformation, is influenced by various determinants. This study utilizes panel data analysis and the pooled least squares method to investigate the factors influencing the share of the blue economy in the archipelagic provinces of Indonesia from 2012 to 2021. With its vast maritime territory and numerous islands, Indonesia provides a highly relevant context for examining these dynamics. The empirical results indicate that information and communication technology (ICT), fisheries capture, and aquaculture production positively impact the blue economy's share. Conversely, trade openness and electricity consumption exhibit a negative relationship with the blue economy's share. Moreover, the analysis reveals that investment does not have a significant effect on the blue economy's share. These findings underscore the critical importance of developing robust infrastructure and implementing stringent regulatory oversight on fishery product trade to enhance sustainable growth within the blue economy framework.
Keywords: 330; blue economy; fisheries; gross domestic product; sustainable development